THE INFLUENCE OF PERCEIVED VALUE AND BRAND EXPERIENCE ON CUSTOMER SATISFACTION AT H&M MANADO TOWN SQUARE - Kezia Putri Wewengkang; Regina T. Saerang (Universitas Sam Ratulangi, 2023)
This study aims to analyze The Influence of Perceived Value and Brand Experience on Customer Satisfaction at Manado Town Square. This study uses quantitative methods and uses multiple linear regression tests to determine the effect of Perceived Value and Brand Experience on Customer Satisfaction. The sample for this study was 100 respondents. The sampling technique used is the purposive sampling method and the data collection method in the form of a questionnaire run through Google Form. Testing and analysis of data in this study using SPSS 22 software. The results showed that Perceived Value (X1) partially had a positive and significant effect on Customer Satisfaction (Y). Brand Experience (X2) has a partial positive and significant effect on Customer Satisfaction (Y). Perceived Value (X1) and Brand Experience (X2) simultaneously have a positive and significant effect on Customer Satisfaction (Y). The R Square value obtained from the result of the coefficient of determination (R2) of 0.651 explains that 65.1% of Customer Satisfaction can be explained by Perceived Value and Brand Experience. Meanwhile, the remaining 34.9% was explained by other variables not studied in this study. Keywords: perceived value, brand experience, customer satisfaction